1977
DOI: 10.1007/bf02124056
|View full text |Cite
|
Sign up to set email alerts
|

Crossing between nondiapausing and diapausing races of Sarcophaga peregrina

Abstract: The temperate race (D) of S. peregrina undergoes pupal diapause in response to certain environmental conditions of photoperiod (13L:11D-11L:13D) and temperature (under 20 degrees C). The tropical race (ND) does not do so under the same circumstances. The tendency toward diapause was suppressed 30-40% of the hybrids of crossings D female x ND male and ND female x Dmale even under such short day and low temperature conditions as 11L:13D-9L:15D, 20 DEGREES C. For entering diapause, the hybrids rrequire a shorter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 6 publications
3
16
0
Order By: Relevance
“…These results suggest that the photoperiodic response is inheritable. Similar results are found in the flesh fly, S. peregrina (Kurahashi and Ohtaki, 1977) and the Asian corn borer, O. furnacalis (Xia et al, 2012), where in the reciprocal crosses between the temperate strain and the tropic strain their F 1 progeny showed a long-day response, similar to that of their parental strains.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results suggest that the photoperiodic response is inheritable. Similar results are found in the flesh fly, S. peregrina (Kurahashi and Ohtaki, 1977) and the Asian corn borer, O. furnacalis (Xia et al, 2012), where in the reciprocal crosses between the temperate strain and the tropic strain their F 1 progeny showed a long-day response, similar to that of their parental strains.…”
Section: Discussionsupporting
confidence: 83%
“…Tropical populations that lack diapause have been crossed with temperate populations in only a few instances (Raina and Bell, 1974;Kurahashi and Ohtaki, 1977;Dingle, 1978;Dingle et al, 1982). Here, we investigated the diapause responses of H. armigera in the pure strains, F 1 and F 2 progeny and backcross progeny by crossing a high diapause response temperate strain with a low diapause response tropical strain under different photoperiods and temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to these investigators, Denlinger (1971) concluded that the embryos of S. crassipalpis in the mother's uterus have photoperiodic sensitivity, and that the photoperiodic experience by the embryos is directly effective on determination of pupa to diapause. The results of our crossing experiments between nondiapausing and diapausing races also suggested that the physiological state of the progeny is determined by combi-nation of genetic and environmental conditions (Kurahashi and Ohtaki , 1977). Vinogradova (1976) proved that the external photoperiodic information is directly perceived by the embryo in S, similis and S. septentrionalis.…”
Section: Introductionmentioning
confidence: 62%
“…Almost all offspring of them undergo pupal diapause in response to a certain environmental condition of photoperiods (13L 11D-1OL 14D) and temperature (20 C) . Under a long day condition (15L 9D) at 20 C, they seldom enter diapause (Kurahashi and Ohtaki , 1977).…”
Section: Methodsmentioning
confidence: 99%